Unraveling the mechanism of ADAMTS13 resistance to protease inhibition - Singh, Kanwal (My University, 2022)
Background: ADAMTS13 is a metalloprotease that regulates the delicate balance between VWF multimeric length and its platelet capturing capacity. Unlike other ADAMTS and coagulation proteases, ADAMTS13 exhibits a prolonged half-life of several days as an active protease, suggesting that it is protected from inhibitors of metalloproteases in blood. Here, we investigate the mechanism by which ADAMTS13 is resistant to protease inhibition. Methods: C-terminal domain truncations of ADAMTS13 (MDTCS and MD) and chimeras with ADAMTS5 (MD13/TCS5, M13/DTCS5, MD5/TCS13, and MD5(TCS-CUB13)) were generated. Metalloprotease domain segments from ADAMTS5 were swapped into MDTCS13 corresponding to the gatekeeper triad (R193, D217, and D252) (MDTCS-G), the variable loop (G236-S263) (MDTCS-V5), and the calcium-binding loop (R180-R193) (MDTCS-C5). MDTCS-GVC5 was generated to study these features simultaneously. Alpha 2-macrogloublin (A2M), tissue inhibitors of metalloproteinases (TIMPs), and small molecule inhibitor (Marimastat) were used as inhibitors, and tested using FRETS-VWF73 and Western blot. Results: MDTCS, MD, MD13/TCS5, M13/DTCS5, MDTCS-G, MDTCS-V5, and MDTCS-C5 constructs were resistant to all inhibitors, whereas MD5/TCS13 was inhibited. The presence of the closed conformation attenuated MD5(TCS-CUB13) proteolysis by 50-fold, while displaying a slower rate of inhibition compared to MD5/TCS13. We report the kinetic parameters of the unique features of the metalloprotease domain (the gatekeeper triad, the variable loop, and the calcium-binding loop). Moreover, simultaneously swapping these features sensitized MDTCS-GVC5 to Marimastat. Conclusion: Our findings reveal that the closed conformation confers global latency, while the metalloprotease domain confers local latency of ADAMTS13. The local latency is maintained by the flexibility of the variable loop and the calcium-binding loop, which fold across the active site cleft to restrict inhibitor and substrate access. Extensive engagement of exosites by VWF can readily displace these loops, thereby activating ADAMTS13 from its latent form. Altogether, we present novel insight into the mechanism by which ADAMTS13 is resistant to protease inhibition.
ADAMTS13 resistance to protease inhibition
Keywords: ADAMTS13; VWF; A2M; TIMP3; Marimastat